Respons Pertumbuhan Benih Kopi Robusta terhadap Waktu Perendaman dan Konsentrasi Giberelin (GA3) - Pertiwi, Novi Mega; Tahir, Muhammad; Same, Made (Politeknik Negeri Lampung, 2016)
Giberellic acid (GA3) is a natural and sintetic grower hormone for speeding up the germination process. The research objective is for knowing the soaking time effect, giberelin (GA3) concentration and the interaction of both factors toward germination and growth of the Robusta coffee seed. This research was carried out in a nursery garden of The State Polytechnic of Lampung, from June 2014 until July 2015. Research arranged by factorial used Randomized Completely Block Design (RCBD). First factor was Giberelin (GA3) concentration i.e. G0 (without GA3), G1 (Giberelin concentration 1000 mg.l-1), G2 (Giberelin concentration 1250 mg.l-1), and G3 (Giberelin concentration 1500 mg.l-1). The second factor was soaking time i.e. A1 (soaking until 12 hours), A2 (soaking until 16 hours), A3 (soaking until 20 hours), and A4 (soaking until 24 hours). The results showed the seed soaking with giberelin (GA3) could affect germinate power, germinated seed quantities, and dry weigh of shoot. There was interaction between giberelin (GA3) concentration and soaking time that could increase germinated seed quantities, leaves wide and dry weigh of shoot.Keywords: Robusta coffee seed, soaking time, giberelin (GA3)Permalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/31